2014
DOI: 10.1177/0004867414527523
|View full text |Cite
|
Sign up to set email alerts
|

Dissociative identity disorder: An empirical overview

Abstract: Objective: Despite its long and auspicious place in the history of psychiatry, dissociative identity disorder (DID) has been associated with controversy. This paper aims to examine the empirical data related to DID and outline the contextual challenges to its scientific investigation. Method: The overview is limited to DID-specific research in which one or more of the following conditions are met: 1) a sample of participants with DID was systematically investigated, 2) psychometrically-sound measures were util… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
99
1
13

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 164 publications
(140 citation statements)
references
References 159 publications
(208 reference statements)
2
99
1
13
Order By: Relevance
“…Moreover, this process seems to be present across trauma, general mental health, and healthy volunteers, indicating a common psychological mechanism. Recent research supports these findings with self-attack and self-criticism manifesting as prominent negative shame coping strategies in multiple populations and predicting mental health difficulties as varied as social anxiety, general anxiety, stress, depression, and poor intimate relationship functioning (Dorahy et al, 2014;Gilbert et al, 2011;Shahar, Doron, & Szepzenwol, 2014). The fact that self-criticism, negative core schemata, and the traumatic experiences shaping Complex Trauma and DID reactions are thought to emerge from early childhood are also suggestive of overlapping pathways (Dalenberg et al, 2012;Kopala-Sibley, Zuroff, Hankin, &, Abela, 2015).…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Moreover, this process seems to be present across trauma, general mental health, and healthy volunteers, indicating a common psychological mechanism. Recent research supports these findings with self-attack and self-criticism manifesting as prominent negative shame coping strategies in multiple populations and predicting mental health difficulties as varied as social anxiety, general anxiety, stress, depression, and poor intimate relationship functioning (Dorahy et al, 2014;Gilbert et al, 2011;Shahar, Doron, & Szepzenwol, 2014). The fact that self-criticism, negative core schemata, and the traumatic experiences shaping Complex Trauma and DID reactions are thought to emerge from early childhood are also suggestive of overlapping pathways (Dalenberg et al, 2012;Kopala-Sibley, Zuroff, Hankin, &, Abela, 2015).…”
Section: Discussionmentioning
confidence: 83%
“…Ironically, "withdrawal" was initially asserted as a psychologically healthy shame coping style (see Nathanson, 1992). Gathering empirical evidence has provided a different picture of this coping style and found that it is both a problematic coping strategy for DID and a risk factor for difficulties in both forming effective therapeutic relationships and overall relationship functioning (Black et al, 2013;Dorahy et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…All participants had a history of child abuse and neglect and had a diagnosis of (1) dissociative disorder (primarily DID), (2) child maltreatmentrelated chronic PTSD or (3) another psychiatric problem. Given the literature showing high levels of abuse and neglect in DID, along with a complex and severe symptom profile (Dorahy et al, 2014), it was expected that the DD sample would have a higher level of childhood abuse/neglect and higher scores on the symptom and affect measures.…”
mentioning
confidence: 99%
“…Another part is that woman when she was an abused child: this part feels and talks like a frightened five-year-old, and knows nothing about having had children or a professional life. The origins of DID Evidence is accumulating (Dorahy et al 2014) to show that Other Specified Dissociative Disorder (OSDD) and DID are linked to severe childhood trauma and abuse. Almost invariably, people with these disorders (DID and OSDD) report years of continuous, most extreme trauma.…”
Section: Dissociative Identity Disordermentioning
confidence: 99%